Exploited Fishery Resources of the Vembanad Lake: Fishery Based on Pokkali Fields and Polders - B., Madhusoodana Kurup; M.J., Sebastian; T.M., Sankaran; P., Rabindranath (Fishery Technology, 2025)
About 2164 ha of Pokkali fields adjacent to Vembanad lake are utilized for the practloe of prawn filtration. ’The total annual production ls 1613.0 t. The seasonal production in these fields varied from 170-18(1) kg/ha and the average yield is computed as 745.4 kg/ha. The catches from Pokkali fields comprised of penaeids such as Metapenaeus dobsoni (66.59%), Penaeus indicus (19.%), M. Monocems (523%) and fishes (8.28%).Six polders namely, Mathikayal, Marthandom, Ranimangalam, C.Block, H.Block and Chithira with an approximate area of 3875 ha are utilized for trapping and holding of fishes in the lower Kuttanad region. The total production is computed at 65.1 t. The catches from the polders comprised of freshwater fishes (93.5%) and palaemonid prawns (6.5%).